2010
DOI: 10.1159/000321538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Vitamins on the Plasma Homocysteine Level in a Free-Living Elderly Population

Abstract: Background: The factors influencing total plasma homocysteine levels (tHcy) are of special interest in the attempt to reduce cardiovascular risk. Aim: This investigation aimed to assess the independent effects of antioxidant vitamins on tHcy in elderly people. Methods: Our cross-sectional analysis included data of 184 subjects (≧60 years) from the longitudinal study in an aging population in Giessen (GISELA), Germany. We examined the effects of plasma levels, intake and supplementation of vitamin C, vitamin E,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…However, the homocysteine elevation seen with TTMF treatment when compared to the baseline is in disagreement with a study in animals, which have demonstrated a beneficial lowering of homocysteine with tocotrienol treatment (Norsidah et al, 2013). One study in humans yielded a neutral effect of tocopherol, rather than tocotrienol, on homocysteine levels (Breilmann et al, 2010). Although the effect observed here is minimal, due to the correlation of homocysteine to cardiovascular risk (Nygård et al, 1995), further studies should aim to confirm this finding and look at the possible mechanisms involved, if any.…”
Section: Tocotrienol-tocopherol and Vitamin C In Hypercholesterolaemimentioning
confidence: 90%
See 1 more Smart Citation
“…However, the homocysteine elevation seen with TTMF treatment when compared to the baseline is in disagreement with a study in animals, which have demonstrated a beneficial lowering of homocysteine with tocotrienol treatment (Norsidah et al, 2013). One study in humans yielded a neutral effect of tocopherol, rather than tocotrienol, on homocysteine levels (Breilmann et al, 2010). Although the effect observed here is minimal, due to the correlation of homocysteine to cardiovascular risk (Nygård et al, 1995), further studies should aim to confirm this finding and look at the possible mechanisms involved, if any.…”
Section: Tocotrienol-tocopherol and Vitamin C In Hypercholesterolaemimentioning
confidence: 90%
“…Both are antioxidants, and as such is thought to reduce oxidative stress and its implications for the human body (Breilmann J et al,2010). One of such implications is atherosclerosis, of which hypercholesterolaemia is a risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…Remaining active in older life improves the quality of life as we age, and a possible link with nutrient intake is promising. Also to be considered, factors influencing total and vitamin C have shown to have a negative association with homocysteine levels 40 …”
Section: Vitamin Cmentioning
confidence: 99%
“…Also to be considered, factors influencing total and vitamin C have shown to have a negative association with homocysteine levels. 40…”
Section: Vitamin Cmentioning
confidence: 99%
“…Therefore, there is a need to look for new agents that can counteract the toxic effects of homocysteine. Good candidates seem to be antioxidants, which, as nonspecific molecules, can inhibit homocysteine-dependent oxidative stress already in the initial phase of the pathological path, that is, at the stage of generation of oxygen free radicals [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%